Efforts to Increase Student Learning Motivation Through the Use of Interactive Learning Media - Eli Mulyani Julaeha; Septi Ernawati; Moh Farid Yusup; Ending; Dede Setiawan (Penerbit Hellow Pustaka, 2025)
This study aims to explore the impact of interactive learning media on student motivation at MA Alhidayah. The research was conducted in two cycles, each comprising planning, implementation, observation, and reflection phases. The results revealed that the initial use of conventional methods showed low student motivation, with only 30% meeting the minimum criteria for mastery. In Cycle I, interactive media such as Quizizz and animated videos were implemented, leading to a significant improvement in motivation and participation, with 70% achieving mastery. The second cycle further refined the approach by introducing creative projects and more interactive strategies, resulting in a significant increase in motivation and academic achievement. By Cycle II, 100% of the students reached the minimum mastery criteria, and motivation increased to 92.5%. The study concludes that interactive learning media, when combined with appropriate teaching strategies, can significantly enhance student motivation and learning outcomes. This finding has practical implications for the use of interactive media in similar educational settings, particularly in integrating religious values with modern learning tools.